2014
DOI: 10.1080/08870446.2014.976645
|View full text |Cite
|
Sign up to set email alerts
|

Parental employment status and adolescents’ health: The role of financial situation, parent-adolescent relationship and adolescents’ resilience

Abstract: The paper deals with parental employment status and its relationship to adolescents' self-reported health. It studies the role of the financial situation, parent-adolescent relationship and adolescent resilience in the relationship between parental employment status and adolescents' self-rated health, vitality and mental health. Multiple regression analyses were used to analyse questionnaire data obtained from 2799 adolescents (mean age 14.3) in 2006. The results show a negative association of the father's, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 43 publications
4
28
0
Order By: Relevance
“…In our study, adolescents with an unemployed father tended to have a poorer QOL. This is consistent with findings from large-scale school-based studies in French and Slovakian adolescents [ 21 , 32 ]. Often, the father provides the primary income in a family.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, adolescents with an unemployed father tended to have a poorer QOL. This is consistent with findings from large-scale school-based studies in French and Slovakian adolescents [ 21 , 32 ]. Often, the father provides the primary income in a family.…”
Section: Discussionsupporting
confidence: 92%
“…Importantly, Ge et al (1994) found that changes in uncontrollable events are associated with increases in depressive symptoms among adolescent girls but not among adolescent boys. More recent research has found a negative association between the father's, but not the mother's, unemployment and adolescents' self-reported health, suggesting that parental gender matters as well (Bacikova-Sleskova et al 2015).…”
Section: Previous Researchmentioning
confidence: 99%
“…On the other hand, children could also benefit, at least in the short term, from their parents' unemployment situation by being able to spend more time with them, therefore being more available to communicate, help, cook, or control bad habits and influences [3,24]. Previous research on parental employment and youths' well-being also suggests that parents' unemployment is associated with young people's lower well-being [8,16,25,26].…”
Section: Introductionmentioning
confidence: 99%